2011
DOI: 10.1111/j.1440-1746.2011.06630.x
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin: A gut hormonal basis of motility regulation and functional dyspepsia

Abstract: Functional dyspepsia (FD) is a functional gastrointestinal disorder (FGID). Several pathophysiological mechanisms have been indicated as possible etiological factors, such as delayed gastric emptying, impaired proximal gastric accommodation and visceral hypersensitivity. Ghrelin is an important gut hormone. It is a motilin-related peptide that was discovered in the stomach, and it acts as an endogenous ligand of growth hormone secretagogue receptor. Ghrelin plays an important role in the stimulation of food in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 53 publications
3
21
0
3
Order By: Relevance
“…Ando et al reported that the preproghrelin gene 3056T->C SNP is associated with changes in the basal ghrelin concentrations (39). It is controversial whether any of the ghrelin gene SNPs alter the levels of ghrelin and/or obestatin (40,41). In this study, we also confirmed that the preproghrelin 3056TT genotype is significantly linked to low levels of acylated ghrelin in H. pylori-negative FD patients compared to healthy volunteers.…”
Section: Discussionsupporting
confidence: 79%
“…Ando et al reported that the preproghrelin gene 3056T->C SNP is associated with changes in the basal ghrelin concentrations (39). It is controversial whether any of the ghrelin gene SNPs alter the levels of ghrelin and/or obestatin (40,41). In this study, we also confirmed that the preproghrelin 3056TT genotype is significantly linked to low levels of acylated ghrelin in H. pylori-negative FD patients compared to healthy volunteers.…”
Section: Discussionsupporting
confidence: 79%
“…Ghrelin has several functions, including regulating the release of somatotropin/growth hormone (GH) from the pituitary gland, where it acts synergistically with the GH-releasing hormone [136][137][138][139]. Moreover, ghrelin accelerates gastric and intestinal motility [140][141][142][143][144][145][146][147][148][149][150][151][152][153]. Ghrelin also increases appetite and feeding and plays a major role in energy metabolism [115,135].…”
Section: Irritable Bowel Syndrome and Appetite-regulating Gut Hormonesmentioning
confidence: 98%
“…Finally, the ghrelin system is also linked to gonadal function (46,47), gut motility (39,48,49,50), and cancer (51,52,53,54), and it is highly likely that this relatively new hormone family will be linked to other medical conditions in the near future.…”
Section: Non-metabolic Actions Of Ag and Dagmentioning
confidence: 99%